Impact of Face Masks and Viewers' Anxiety on Ratings of First Impressions from Faces. (January 2022) - Guo, Kun; Hare, Alexander; Liu, Chang Hong
Face mask is now a common feature in our social environment. Although face covering reduces our ability to recognize other's face identity and facial expressions, little is known about its impact on the formation of first impressions from faces. In two online experiments, we presented unfamiliar faces displaying neutral expressions with and without face masks, and participants rated the perceived approachableness, trustworthiness, attractiveness, and dominance from each face on a 9-point scale. Their anxiety levels were measured by the State-Trait Anxiety Inventory and Social Interaction Anxiety Scale. In comparison with mask-off condition, wearing face masks (mask-on) significantly increased the perceived approachableness and trustworthiness ratings, but showed little impact on increasing attractiveness or decreasing dominance ratings. Furthermore, both trait and state anxiety scores were negatively correlated with approachableness and trustworthiness ratings in both mask-off and mask-on conditions. Social anxiety scores, on the other hand, were negatively correlated with approachableness but not with trustworthiness ratings. It seems that the presence of a face mask can alter our first impressions of strangers. Although the ratings for approachableness, trustworthiness, attractiveness, and dominance were positively correlated, they appeared to be distinct constructs that were differentially influenced by face coverings and participants' anxiety types and levels.